2021
DOI: 10.1016/j.cmi.2020.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Detection of multiple hypervirulent Klebsiella pneumoniae strains in a New York City hospital through screening of virulence genes

Abstract: Objectives: The 'hypervirulent' variant of Klebsiella pneumoniae (hvKp) is a predominant cause of community-acquired pyogenic liver abscess in Asia, and is an emerging pathogen in Western countries. hvKp infections have demonstrated 'metastatic' dissemination in immunocompetent hosts, an unusual mode of infection associated with severe complications. Two cases alerted us to the possible presence of hvKp at our hospital, both involving elderly Hispanic males who presented with recurrent fever, bacteraemia, epig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
66
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(76 citation statements)
references
References 34 publications
9
66
1
Order By: Relevance
“…Furthermore, a comprehensive review of English language literature revealed only one previous report of K. quasipneumoniae isolated from liver, so our exclusive isolation of K. quasipneumoniae from liver specimens remains somewhat unexpected[54].We observed an isolation rate of 5.7% (n=2) for hvKp in our collection of sterile site specimens from Strong Memorial Hospital from between October 2018 and October 2019. This rate is consistent with the limited previous studies of the rate of hvKp in North American hospitals, with a rate of 8.2% found in Calgary, Alberta, Canada, rates of 7.9% and 3.9% in different hospitals in Houston, Texas, USA, and a rate of 3.7% in a New York City, New York, USA hospital[42,43,60]. Two of these studies, Periano et aland Chou et al, collected only blood isolates, while Parrott et al collected isolates from a variety of clinical specimens, predominantly blood.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…Furthermore, a comprehensive review of English language literature revealed only one previous report of K. quasipneumoniae isolated from liver, so our exclusive isolation of K. quasipneumoniae from liver specimens remains somewhat unexpected[54].We observed an isolation rate of 5.7% (n=2) for hvKp in our collection of sterile site specimens from Strong Memorial Hospital from between October 2018 and October 2019. This rate is consistent with the limited previous studies of the rate of hvKp in North American hospitals, with a rate of 8.2% found in Calgary, Alberta, Canada, rates of 7.9% and 3.9% in different hospitals in Houston, Texas, USA, and a rate of 3.7% in a New York City, New York, USA hospital[42,43,60]. Two of these studies, Periano et aland Chou et al, collected only blood isolates, while Parrott et al collected isolates from a variety of clinical specimens, predominantly blood.…”
supporting
confidence: 92%
“…Since its initial characterization, hvKp has become a leading cause of community acquired liver abscess, gram negative pneumonia and bacterial meningitis in Taiwan and is an emerging cause of necrotizing fasciitis [30][31][32][33][34][35][36][37][38][39]. HvKp has also been identified worldwide, [40] though there have been few systematic studies of hvKp in the United States [41][42][43].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Case reports indicate that hvKp strains exist in the U.S., but their prevalence is unclear and has only been investigated in two surveillance studies (24,25). In this work, we determined the prevalence of hvKp at NMH by identifying isolates using diagnostic criteria of hvKp.…”
Section: Discussionmentioning
confidence: 99%
“…CC-BY-NC-ND 4.0 International license available under a (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity. It is made common in Asia, but little is known about their prevalence in the U.S. Case reports document the presence of hvKp infections and PLA in North America, but only a few surveillance studies have been performed (21,(24)(25)(26). hvKp strains frequently express a highly mucoid capsule, leading to a "hypermucoviscous" colony phenotype, and are considerably more virulent in mouse models than cKp strains (23).…”
Section: Introductionmentioning
confidence: 99%